Ile‐Lys‐Val‐ala‐Val (IKVAV) peptide for neuronal tissue engineering. (4th October 2018) - Patel, Rajkumar; Santhosh, Mallesh; Dash, Jatis Kumar; Karpoormath, Rajshekhar; Jha, Amitabh; Kwak, Jeonghun; Patel, Madhumita; Kim, Jong Hak
Abstract : Despite the great advances in microsurgery, some neural injuries cannot be treated surgically. Stem cell therapy is a potential approach for treating neuroinjuries and neurodegenerative disease. Researchers have developed various bioactive scaffolds for tissue engineering, exhibiting enhanced cell viability, attachment, migration, neurite elongation, and neuronal differentiation, with the aim of developing functional tissue grafts that can be incorporated in vivo. Facilitating the appropriate interactions between the cells and extracellular matrix is crucial in scaffold design. Modification of scaffolds with biofunctional motifs such as growth factors, drugs, or peptides can improve this interaction. In this review, we focus on the laminin‐derived Ile‐Lys‐Val‐Ala‐Val peptide as a biofunctional epitope for neuronal tissue engineering. Inclusion of this bioactive peptide within a scaffold is known to enhance cell adhesion as well as neuronal differentiation in both 2‐dimensional and 3‐dimensional environments. The in vivo application of this peptide is also briefly described.